2018
DOI: 10.1007/s00335-018-9736-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual susceptibility to arsenic-induced diseases: the role of host genetics, nutritional status, and the gut microbiome

Abstract: Arsenic (As) contamination in water or food is a global issue affecting hundreds of millions of people. Although As is classified as a group 1 carcinogen and is associated with multiple diseases, the individual susceptibility to As-related diseases is highly variable, such that a proportion of people exposed to As have higher risks of developing related disorders. Many factors have been found to be associated with As susceptibility. One of the main sources of the variability found in As susceptibility is the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 157 publications
0
18
0
Order By: Relevance
“…Human exposures to arsenic are linked to a range of sources and exposure pathways, with individual intakes varying widely by location, employment, gender, age, and other characteristics that differ across individuals and populations ( Chi et al. 2018 ; Minatel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Human exposures to arsenic are linked to a range of sources and exposure pathways, with individual intakes varying widely by location, employment, gender, age, and other characteristics that differ across individuals and populations ( Chi et al. 2018 ; Minatel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the affected population are exposed to arsenic primarily through drinking water and food. Several studies have described the mechanism of arsenic metabolism inside human biological system ( 15 17 ). The inorganic form of oxy-anions, including pentavalent arsenite (H 2 ) and trivalent arsenate (H 3 AsO 3 ) is present abundantly in natural water.…”
Section: Understanding the Present State Of Researchmentioning
confidence: 99%
“…Another pathway of arsenic metabolism shows sequential addition of methyl groups to trivalent arsenicals and its conjugation with glutathione generating intermediate derivatives like arsenic triglutathione (ATG), monomethyl arsenic diglutathione (MADG), and dimethyl arsenic glutathione (DMAG). A third pathway explained about the formation of iAs/protein conjugate and subsequent generation of methylated metabolites ( 17 ). Various studies have also shown effect of folate intake and folate metabolism on arsenic metabolism and related disease risks.…”
Section: Understanding the Present State Of Researchmentioning
confidence: 99%
“…Chi et al . () review how human genetics, lifestyle and diet will influence individual susceptibility to As‐related diseases. We offer to continue this dialogue but explicitly from the perspective of the GIT microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic research in the GIT microbiome is in a relative state of infancy and can benefit from an early exchange of ideas, concepts and views. Chi et al (2018) review how human genetics, lifestyle and diet will influence individual susceptibility to As-related diseases. We offer to continue this dialogue but explicitly from the perspective of the GIT microbiome.…”
Section: Introductionmentioning
confidence: 99%